Out-of-Place and In-Place Policing: An Examination of Traffic Stops in Racially Segregated Philadelphia - Hannon, Lance (Crime & delinquency, 2021)
It is commonly argued that Black people may be more likely to be stopped by the police in majority White neighborhoods due to a natural tendency to first observe and then scrutinize that which seems out of the ordinary. Anecdotal evidence of police officers appearing equally drawn to White people in predominantly Black neighborhoods is sometimes presented to suggest that the phenomenon is race neutral. Motivated by such narratives, we examine the extent to which Black versus White racial categorization encourages police scrutiny in out-of-place and in-place contexts. Applying the veil-of-darkness and vehicle search threshold tests, we find that in place or out of place, being seen as White is always an advantage in Philadelphia.